2021
DOI: 10.1038/s41598-021-82676-5
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle and behavioral modifications made by patients with interstitial cystitis

Abstract: Interstitial cystitis/bladder pain syndrome (IC/BPS) negatively affects the quality of life. In this study, we investigated the lifestyle behavioral changes patients with IC/BPS make to cope with their symptoms. This prospective study was conducted between August 2018 and June 2019. All patients had a primary symptom of suprapubic pain with a full bladder and other lower urinary tract symptoms for more than 6 weeks as well as cystoscopic findings. All participants completed our self-developed questionnaire, wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
(50 reference statements)
0
9
0
Order By: Relevance
“…Our previous study indicated that some patients with IC/BPS had an average onset time of 6 years before their diagnosis was verified. [ 6 ] An extended duration between the onset of urinary symptoms and the final diagnosis of IC/BPS was also reported by Driscoll et al [ 4 ] Because the symptoms of IC/PBS overlap with those of OAB, sophisticated differential diagnosis of both conditions is crucial for further proper management.…”
Section: Introductionmentioning
confidence: 71%
“…Our previous study indicated that some patients with IC/BPS had an average onset time of 6 years before their diagnosis was verified. [ 6 ] An extended duration between the onset of urinary symptoms and the final diagnosis of IC/BPS was also reported by Driscoll et al [ 4 ] Because the symptoms of IC/PBS overlap with those of OAB, sophisticated differential diagnosis of both conditions is crucial for further proper management.…”
Section: Introductionmentioning
confidence: 71%
“…On the other hand, there is a debate about whether the effects are significant [9]. Moreover, it is unclear how much IC/BPS is affected by recurrent UTIs, but clinically, many patients are taking cranberries to improve their symptoms [1].…”
Section: Discussionmentioning
confidence: 99%
“…Although they have been deemed ineffective for treating urinary tract infections (UTIs), there is evidence suggesting that cranberry juice may reduce the number of symptomatic UTIs [1]. In addition, the intravesical instillation of hyaluronic acid and chondroitin sulfate is widely used, which relieves pain by replenishing the bladder mucosal glycosaminoglycan (GAG) layer damaged by inflammation [2][3][4].…”
mentioning
confidence: 99%
“…92 Results of most studies proved that BoNT-A can decrease the exocytosis of proinflammatory and excitatory neurotransmitters and neuropeptides, such as substance P, from primary afferent fibers that transmit nociceptive pain and participate in the development of peripheral and central sensitizations and decreases the insertion of pain-sensitive ion channels. 93 Seven studies discussed lifestyle and psychological therapies such as CBT or mindfulness, [94][95][96] hypnosis, 97 lifestyle modification, 98 yoga, 99 and e-health application. 100 Seven studies focused on treatment with oral medications, including Th2 cytokine inhibitor suplatast tosilate, 101 α1 adrenoceptor blocker silodosin, 102 SHIP1 of amino acid protein activator, 103 fatty acid amide hydrolase inhibitor ASP3652, 104 anti-TNF-α agent, 105 phosphodiesterase type 5 inhibitor tadalafil, 106 and pentosan polysulfate sodium.…”
Section: Current Treatment Modalities and Constructing Diagnostic And...mentioning
confidence: 99%
“…118,119 According to these studies, LESW and PTNS/TENS could improve bladder symptoms in most NHIC patients, [108][109][110]113,116,117 whereas education, CBT, and lifestyle modification might assist patients in coping with their symptoms regardless of their bladder condition. 96,98,100 PFMP may benefit from a combination of pelvic floor muscle treatment in patients who have pelvic floor myofascial pain. 119 Most experimental studies have indicated that the trigger points of PFMP contribute to peripheral and central sensitizations because they can affect peripheral nociceptors, spinal dorsal horn neurons, and brainstem.…”
Section: Current Treatment Modalities and Constructing Diagnostic And...mentioning
confidence: 99%